Comparison of L-Threonine Aldolase Variants in the Aldol and Retro-Aldol Reactions - Fesko, Kateryna (Frontiers in Bioengineering and Biotechnology, 2019)
Most of biochemical and mutagenesis studies performed with L-threonine aldolases were done with respect to natural activity, the cleavage of L-threonine and sometimes L-beta-phenylserine. However, the properties of variants and the impact of mutations on the product synthesis are more interesting from an applications point of view. Here we performed site-directed mutagenesis of active site residues of L-threonine aldolase from Aeromonas jandaei to analyze their impact on the retro-aldol activity and on the aldol synthesis of L-beta-phenylserine and L-alpha-alkyl-beta-phenylserines. Consequently, reduced retro-aldol activity upon mutation of catalytically important residues led to increased conversions and diastereoselectivities in the synthetic direction. Thus, L-beta-phenylserine can be produced with conversions up to 60% and d.e.‘s up to 80% (syn) under kinetic control. Furthermore, the donor specificity of L-threonine aldolase was increased upon mutation of active site residues, which enlarged the pocket size for an efficient binding and stabilization of donor molecules in the active site. This study broadens the knowledge about L-threonine aldolase catalyzed reactions and improves the synthetic protocols for the biocatalytic asymmetric synthesis of unnatural amino acids.